2021
DOI: 10.5194/ems2021-232
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benefit of microwave radiometer and cloud radar observations for data assimilation and fog process studies during the SOFOG3D experiment

Abstract: <p>Fog forecasts still remain quite inaccurate due to the complexity, non linearities and fine scale of the main physical processes driving the fog lifecycle. Additionally to the complex modelling of fog processes, current numerical weather prediction models are known to suffer from a lack of operational observations in the atmospheric boundary layer and more generally during cloudy-sky conditions. Continuous observations of both thermodynamics and microphysics during the fog lifecycle are thus e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…SOFOG3D (SOuth west FOGs 3D experiment) was a project that was conducted from October 2019 to April 2020 in France over 300×300 km, where eight MWRs were used. The data from this campaign have been presented at scientific conferences so far (e.g., Martinet et al, 2021;Vishwakarma et al, 2021;Burnet et al, 2020). The reason for the use of MWR during the SOFOG3D campaign was the article Martinet et al (2020), which showed the improvement of numerical weather prediction models by assimilation of MWR data.…”
Section: Introductionmentioning
confidence: 99%
“…SOFOG3D (SOuth west FOGs 3D experiment) was a project that was conducted from October 2019 to April 2020 in France over 300×300 km, where eight MWRs were used. The data from this campaign have been presented at scientific conferences so far (e.g., Martinet et al, 2021;Vishwakarma et al, 2021;Burnet et al, 2020). The reason for the use of MWR during the SOFOG3D campaign was the article Martinet et al (2020), which showed the improvement of numerical weather prediction models by assimilation of MWR data.…”
Section: Introductionmentioning
confidence: 99%